Hubungan Shyness dengan Kecemasan Sosial Mahasiswa Baru Perantau dari Luar Jawa - Dwi Hastuti, Dyah Ayu; Kutub Hardew, Ayatullah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Continuous shyness can be the main trigger for the formation of social anxiety that limits a person’s ability to interact and adapt in a social environment. The aim of this study was to find out the relationship between shyness and social anxiety of nomadic new students from outside Java. This research method is quantitatively correlational using the purposive sampling technique. The population in this study consisted of nomadic new students from oustside Java who attended universities around Solo Raya. The sample was 151 respondents. Psychological scale with Likert scale model consisting of Revised Cheek and Buss Shyness Scale (RCBS) and Social Anxiety Scale Adolescent. It means that among new students, nomads from outside Java have a positive relationship between shyness and social anxiety. Keywords: Shyness; Social Anxiety; Fresher